Management Model of Unda River in the Development of Traditional Village Based on Custom Village in Paksebali Village Klungkung Bali - I Made Suwitra; I Wayan Subawa; Diah Gayatri Sudibya; I Wayan Arthanaya; Ni Putu Sawitri Nandari (RIRAI Publisher, 2021)
This research is intended to identify the water resources management model carried out by Paksebali Village in the development of Tourism Villages in Klungkung Regency. Water resources (SDA) managemet in the development of tourism villages through coexistence between the Customary Villages and the Dinas (state) Villages which are oriented towards empowering rural communities for community welfare. So the Paksebali Village can coexit both the legal structure and the legal substance of the use of Unda River's surface water as a water attraction, restaurant, prewed in the development of new tourist destinations in Klungkung Regency through the development of a tourism village.